The effect of manganese and carbon on the mechanical properties of the welded layer of the bucket teeth of the Hadfield steel excavator - S.F. Posonskyi (Проблеми трибології)
The paper investigates the effect of the surfacing composition’s chemical structure (the manganese and carbon concentrations’ ratio) on the mechanical properties of the surfacing layer on Hadfield steel for increasing the durability of the products made from it, namely the excavator bucket’s teeth.  Two criteria, namely the impact toughness and wear resistance of the coating, were chosen as optimization parameters. The assessment of the impact strength of the deposited coating was carried out on the Sharpie samples on the pendulum copra, and the wear test was carried out according to the Brinly-Haworth scheme in the conditions of samples’ abrasion with quartz sand. Wear resistance of Hadfield steel, containing 1.1% C and 13% Mn, was taken as a unit of wear resistance in these experiments. To determine the optimal coating modes, the active experiment with the application of mathematical planning methods was conducted. The obtained response surfaces and graphs of equal output lines make it possible to establish the level of studied factors’ influence on the optimization parameter. In order to analyze the influence of given factors on the optimization criteria, scatter plots with histograms were constructed, which make it possible to determine the rational values ​​of the selected optimization criteria graphically - impact toughness and wear resistance of the coating